(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The aim of the research article is to study various aspects of the conflictoccurrence, which is very relevant problem of the modern society, including in Kazakhstan.The article presents an attempt to reveal the social nature of national, racial, ethnic and religious conflicts.To achieve the goals, the research is carried outon the nature of social conflicts by determining their role.The modern conflictological paradigm reflecting the globalization of the societyis considered on the example of Kazakhstan.An attempt to resolve these conflictswas made. Identify typological characteristics of the conflicts and provide examples of data collision in the society’s interpretations, normative-holistic, deprivation, civilizational and intra cultural areas.The forms and types of dialogue as the most fruitful mechanism for resolving socio-cultural conflicts are analyzedtoday. Key words: ideology, identity, socio-cultural conflict, civilization, nation, race.